Ergonomic Interventions in the Implementation of Risk-Based Audit to Overcome Dysfunctional Auditor Behavior - Anggraini, Putri; Istianah, Iis (Jurnal Tata Kelola dan Akuntabilitas Keuangan Negara, 2022)
It is undeniable that auditors are expected to develop a strong audit plan to produce value-added audit reports. Given the preceding, current practice in auditing shows that many auditors use Risk-Based Audit (RBA) to determine an appropriate audit scope. RBA could effectively guide auditors to define audit scope based on the assessed risk. However, RBA does not consider human factors in performing audits. Consequently, most auditors encounter time budget pressure in meeting tight audit deadlines. Such an issue could adversely affect auditors' productivity and health. On the other hand, ergonomics is a discipline that focuses on human capabilities in completing tasks. The study also guides employees to adapt to the job while improving their well-being and increasing the quality of work results. Therefore, this study aims to intervene the principles of RBA with ergonomics. RBA consists of three stages: risk assessment, response, and reporting. The authors have concluded that ergonomics could intervene in RBA in the risk response step once the risk level is determined in the risk assessment phase by conducting a literature review study. Therefore, the auditors should balance the time budget allocation based on the assessed audit risk (low, moderate, or high). As the entity's risk is high, the audit team should be given an extended time allocation and vice versa. The findings suggest that auditors should develop an appropriate time budget scheme for specific audit procedures based on the assessed risks resulting from RBA implementation.